Memposisikan Perpustakaan Daerah dalam Pengembangan E-Government Indonesia - Wawan Wiraatmaja; Kudang Boro Seminar (Jurnal Pustakawan Indonesia, 2006)
This paper tries to show the position of the public library as one of the local devices in developing e-government in Indonesia. It is described about the egovernment and how important is the integral understanding to a variety of the government elements in supporting the development. The description is based on the understanding of the Indonesian government model with its current local autonomy which give the local government a huge power to execute the government functions. The library is directed as the information dissemination elements and the coomunication device between the local goverment and thesociety.